IDENTIFIKASI ASPEK SENSE OF PLACE KAWASAN BERSEJARAH BERDASARKAN PREFERENSI PENGUNJUNG (Studi Kasus: Kawasan Sagan, Yogyakarta) - Pramudito, Sidhi; Kristiawan, Yanuarius Benny; Wismarani, Yustina Banon; Analisa, Fabiola Chrisma Kirana (Jurnal Arsitektur ARCADE, 2020)
Sagan area is one of the historical regions in Yogyakarta. This area has a characteristic of the Dutch colonial heritage that visitors can still feel when they are there. These characteristics then become the region's identity that can give a particular feeling or impression to visitors, or can be called a sense of place. A sense of place is an essential aspect of architecture so that a design is maintained. A sense of place is defined as the bond between place and humans, which can be obtained from a combination of physical settings, activities, and meaning. This study aims to identify aspects of the sense of place, as seen from visitor preferences. The thing observed is related to the activity, physical settings, and what is felt by visitors. By knowing the preferences of visitors, it is hoped that it can be used to create a sense of place that suits the demands of today's needs. This research was conducted qualitatively and exploratively using a grounded theory approach. Data is collected through open-ended questionnaires about what respondents experienced. The data is then processed qualitatively by the method of open coding, axial coding, and selective coding. The results showed that aspects of the Sagan region's physical setting, which are still preserved in the form of simple indische architectural features and tropical architecture, are the dominant factors that can create a sense of place. But based on an analysis of visitor preferences, changes in building functions are also needed to strengthen the sense of place of the Sagan region. Building functions that fit the character of today's visitors help visitors to feel the physical setting typical of the Sagan region. Thus it can be concluded that the sense of place can not only be formed by preserving its physical settings but also needs to be conducted a review of human preferences as actors who play a role in it.